Production of bioplastics from hydrolysates of paper industry by Haloferax mediterranei - Ferreira, Diana Filipa Cabecinhas (2018)
The biorefinery concept has attracted much attention over the last decade due to increasing concerns about the use of fossil resources. In this context emerged the use of bioplastics, namely polyhydroxyalkanoates (PHA). PHA are biocompatible and biodegradable plastics that can be obtained from renewable raw materials and can constitute an alternative solution to conventional plastics. In this work, hydrolysed cellulose pulp, coming from Eucalyptus globulus wood cooking, was used as substrate to the PHA-storing bacteria Haloferax mediterranei. The hydrolysed pulp is rich in simple sugars, mainly glucose (81.96 g.L-1) and xylose (20.90 g.L-1). Tests were made in defined medium with glucose and xylose and in hydrolysate supplemented with salts and yeast extract. Different concentrations of glucose were tested, namely 10, 15, 20, 30 and 40 g.L-1. The best accumulation results (27.1 % of PHA) were obtained in hydrolysate medium with 10 g.L-1. Using this concentration, assays were performed in fed-batch and sequencing batch reactor conditions in order to determine the best feeding strategy. The strategy that led to the best results was fed-batch assay with 24.7 % of PHA. An assay without sterile conditions was performed, in which was obtained the same growth than in sterilization test. Finally it was performed an assay in a bioreactor and a fast growth (0.14 h-1) with high glucose and xylose consumption rates (0.368 g.L-1.h-1 and 0.0947 g.L-1.h-1, respectively) were obtained. However 1.50 g.L-1 of PHA, corresponding to 16.1 % (92.52 % of 3HB and 3HV of 7.48 %) of % PHA were observed. The polymer was further characterized by DSC with a glass transition temperature of -6.07 °C, a melting temperature of 156.3 °C and a melting enthalpy of 63.07 J.g-1, values that are in accordance with the literature. This work recognizes for the first time the suitability of the pulp paper hydrolysate as a substrate for PHA production by H. mediterranei.